Alcohol-related Outcomes and All-cause Mortality in the Health 2000 Survey by Participation Status and Compared with the Finnish Population - McMinn, Megan A. (Epidemiology, 2020)
In the context of declining levels of participation, understanding differences between participants and non-participants in health surveys is increasingly important for reliable measurement of health-related behaviors and their social differentials. This study compared participants and non-participants of the Finnish Health 2000 survey, and participants and a representative sample of the target population, in terms of alcohol-related harms (hospitalizations and deaths) and all-cause mortality. METHODS: We individually linked 6,127 survey participants and 1,040 non-participants, aged 30–79, and a register-based population sample (n = 496,079) to 12 years of subsequent administrative hospital discharge and mortality data. We estimated age-standardized rates and rate ratios for each outcome for non-participants and the population sample relative to participants with and without sampling weights by sex and educational attainment. RESULTS: Harms and mortality were higher in non-participants, relative to participants for both men (rate ratios = 1.5 [95% confidence interval = 1.2, 1.9] for harms; 1.6 [1.3, 2.0] for mortality) and women (2.7 [1.6, 4.4] harms; 1.7 [1.4, 2.0] mortality). Non-participation bias in harms estimates in women increased with education and in all-cause mortality overall. Age-adjusted comparisons between the population sample and sampling weighted participants were inconclusive for differences by sex; however, there were some large differences by educational attainment level. CONCLUSIONS: Rates of harms and mortality in non-participants exceed those in participants. Weighted participants’ rates reflected those in the population well by age and sex, but insufficiently by educational attainment. Despite relatively high participation levels (85%), social differentiating factors and levels of harm and mortality were underestimated in the participants.